Loss of foundation species revisited: conceptual framework with lessons learned from eastern hemlock and whitebark pine. Issue 11 (8th November 2019) - Degrassi, Allyson L.; Brantley, Steven; Levine, Carrie R.; Mohan, Jacqueline; Record, Sydne; Tomback, Diana F.; Ellison, Aaron M.
Abstract: Ecologists and conservation biologists often prioritize the study of species that are declining, threatened, or endangered over species that are abundant and ecologically important, such as foundation species (FS). Because entire ecosystems and their biodiversity depend on FS, we argue that they have high conservation priority. A citation analysis reveals that FS are studied, but often are characterized ambiguously. More effort is needed to identify FS before they, and the ecosystems they define, are at risk of decline or loss. We suggest a new conceptual framework that includes: informed identification of FS in ecosystems; documentation of ecosystem services provided by FS; a long‐term monitoring strategy to detect threats to FS within specified ecosystems; and, if threats are identified, a comprehensive conservation and adaptive management strategy for FS. We use two widely distributed, rapidly declining North American foundation tree species ( Tsuga canadensis [eastern hemlock] and Pinus albicaulis [whitebark pine]) to illustrate this framework. These species exemplify the importance of identifying FS early and conserving or restoring them when they are threatened.